A Review of Latin American Integration: From LAFTA to LAIA - Villarreal García, Julio Francisco; Portugal Jesus, Lua Haylee; Carrion Loyola, Andrea Alejandra; Quispe Robles, Jhoan Luis (Universidad Pedagógica y Tecnológica de Colombia, 2023)
This paper aims to analyze the reasons for the failure of LAFTA and, specifically, the causes of the reorganization that led to the formation of LAIA. In this sense, this article will not only appeal to an economic perspective, since it will inquire into political-social matters related to the character and purposes of regional integrations. The method used for this economic and historical analysis is based on a bibliographical review of economic integration mechanisms in Latin America. This will account for the course from LAFTA to LAIA in the light of the relative decline of the former in its last years. The results show that the main reasons for the failure of LAFTA can be explained by the diversity of readings that its own founding States made about  the objective of the association, the lack of a consolidated political-economic program and the infeasibility of the negotiations within the framework of the common and national lists. The study of such a failure, in short, will allow us to give the concrete material and commercial consequences of the conclusion of a free trade between states with dissimilar economic development, analysis that is still relevant today.